Parables unplugged : reading the lukan parables in their rhetorical context - Thurén, Lauri (Fortress Press, 2014)
The parables of Jesus have long been read either as allegories encoding Christian theology or as tantalizing clues to the authentic voice of Jesus. Thuren proposes instead to read the parables "unplugged" from any assumptions beyond those given in the narrative situation in the text, on the common-sense premise that the very form of the parable works to propose a (sometimes startling) resolution to a particular problem. Thuren applies his method to the parables in Luke, exploring the Evangelist's specific narrative purposes in the use of individual parables.